Predicting the biomechanics in aramany class i obturator prostheses using different designs and materials: a combined finite element modeling and experimental study - Mousa, Mohammed Assayed Mohammed Assayed (2024)
There is a direct relationship between biomechanics and the success of maxillofacial prostheses (MFPs). The linear (LDP) and tripodal designs (TDP) are the only designs used for unilateral MFPs. Besides, most literature showed only Co-Cr-based obturators. This study explored the biomechanics in obturators for Aramany's Class I defect using a new design named fully tripodal (FTDP) and seven materials in terms of retention, stress, and strain using finite element analysis (FEA), photoelastic stress analysis (PESA), digital image correlation (DIC), and a universal testing machine. Nine FE models, 30 epoxy resin models (12 for PESA and 18 for DIC), and 54 frameworks divided into nine for AP retained with Adam's clasps, LDP, TDP, FTDP, PEEK-based, and biotone-based MFPs were fabricated from casts obtained from archived scanned human skull. The data on retention, PESA, DIC, and FEA data were collected and evaluated to identify the displacement, stress, and strain in the MFPs with assorted designs and materials. Regarding retention, there were no significant differences between FTDP and TDP regarding retention, stress, and strain. Regarding the materials, the metalbased produced the highest retention, the highest stress on the abutments, and the lowest stress and strain on the defective side. The flexible materials-based MFPs demonstrated the lowest retention, the lowest stress and strain on the abutments of the contralateral side, and the highest stress and strain on the defective side (P<0.05).